Bhagavāna Śrī Rshabhadeva (Hiraṇyagarbha) kī mahān śramaṇa yoga paramparā meṃ yogūnuśīlana = Exploring the pinnacles of yoga - Bāṛhadāra, Kailāśa Canda, 1913- (Prabandhakāriṇī Kameṭī, Digambara Jaina Atiśaya Kshetra Śrī Mahāvīrajī, 1982)
Digambara Jaina approach to Yoga.